Spatial pattern of geodiversity assessment in the Marrecas River drainage basin, Paraná, Brazil - F.C. Manosso (Elsevier, 2021)
Geodiversity refers to the variety of abiotic elements and processes present at different scales and dimensions in an area. In this study, the combination of geological formations, structural lineaments and dikes, geomorphological compartments, soil classes, relief, hydrographic systems, and climatic aspects is considered as the geodiversity of the Marrecas River drainage basin in the south-western region of the state of Paraná, southern Brazil. These components were superimposed on a regular 2 × 2 km grid map (1:250,000) and geodiversity indices were applied to quantify and assess the variation of their distribution along the Marrecas River drainage basin. The results indicate a lower geodiversity on some interfluves and in the river estuary area with a homogeneous relief. On the other hand, higher geodiversity rates were detected in several valleys, which contain a greater variation of abiotic elements because they are embedded and dissected. Common diversity indices, which are generally used in biodiversity studies, were used to determine the distribution of the geodiversity richness in the study area, such as: Shannon, Simpson’s, E-Pielou, Margalef and Menhinick indices. Similar to the biodiversity, the assessment of the geodiversity should not be restricted to the richness but should also include the spatial distribution of environmental components in the study area according to frequency levels. The results show that geographic objects, which are continuous rather than discrete, are more useful and the absence of standards regarding the assessment of the geodiversity. Continuous data should be preferred as basic data for any area.